Slip modulus of cold-formed steel members sheathed with wood structural panels - Northcutt, Amy L.; Kramer, Kimberly Waggle (My University, 2015)
Cold-formed steel framing sheathed with wood structural panels is a common method of construction for wall, roof and floor systems in cold-formed steel structures. Since wood structural panels are attached with screws at relatively close spacing, a certain amount of composite behavior will be present. The benefit of composite behavior is not currently being taken advantage of in the design of these structural systems. While composite effects are present, they are not yet being accounted for in design due to a lack of statistical data. To determine the amount of composite action taking place in these systems, the slip modulus between steel and wood is required. The slip modulus reflects the amount of shear force able to be transferred through the screw connection, to either member of the composite system. This paper presents the results of a study conducted to determine values of the slip modulus for varying thicknesses of cold-formed steel and plywood sheathing. Shear tests were conducted and the slip moduli were determined based on ISO 6891 and ASTM D1761. Compared with data from a previous preliminary study performed by others, the slip modulus values determined from these tests were deemed reasonable. The determination of the slip modulus will lead to the ability to calculate a composite factor. Determination of a composite factor will allow cold-formed steel wood structural panel construction to become more economical due to the available increase in bending strength.
Maher, J. E., & Kramer, K. W. (2007). LEED-NC version 2.2 rating system applications of common structural materials. Paper presented at the Sustainable Construction Materials and Technologies - International Conference on Sustainable Construction Materials and Technologies, 549-562.
Keywords: Steel structures; Cold-formed steel; Composite behavior; Floor systems; Shear force; Slip modulus